Synthesis of Novel Heterocyclic Derivatives with Potential Bioactivity Using Modern Catalytic Techniques - Gamal Aboulgasem; Mahdi Almaky; Waheebah Suwayd; Abdulwahab Tuwati (African Journal of Advanced Pure and Applied Sciences, 2026)
The present study reports the design, synthesis, characterization, and biological evaluation of three novel series of heterocyclic derivatives, comprising pyrazole-pyrimidine hybrid compounds (Series A, compounds 1–6), N-substituted indole derivatives (Series B, compounds 7–12), and oxazole-thiazolidine conjugates (Series C, compounds 13–18), employing modern catalytic strategies including zinc oxide nanoparticle (ZnO NP) catalysis, palladium-copper dual homogeneous catalysis, and L-proline organocatalysis. Comprehensive reaction condition optimization through systematic variation of catalyst type, loading, solvent, and temperature afforded products in isolated yields ranging from 68 to 92% under mild and environmentally favorable conditions. All synthesized compounds were rigorously characterized by ¹H NMR, ¹³C NMR, mass spectrometry (MS), infrared (IR) spectroscopy, and elemental analysis. Biological evaluation through in vitro antimicrobial and anticancer assays revealed that several compounds exhibited remarkable pharmacological activity. Compound 8 demonstrated the highest anticancer potency, with IC₅₀ = 3.20 μM against MCF-7 breast cancer cells and a selectivity index of 26.7 relative to normal cells, surpassing the reference drug doxorubicin. Compound 7 showed potent broad-spectrum antibacterial activity with a minimum inhibitory concentration (MIC) of 0.78 μg/mL against Staphylococcus aureus. Comprehensive structure–activity relationship (SAR) analysis linked electron-withdrawing substitution patterns to enhanced bioactivity across all series. The ZnO NP catalyst demonstrated exceptional recyclability over five consecutive cycles with less than 5.4% decline in yield. This research contributes meaningfully to the development of efficient, selective, and sustainable catalytic routes for the preparation of pharmacologically promising heterocyclic scaffolds.